Imagining Transnational Virus In The Digital Sphere – A Case Study Of Zika Virus During 2016 Rio Olympic Games - Kim, Young Rim (AoIR Selected Papers of Internet Research, 2017)
How do the public imagine contagion? The objective of this research is to examine how infectious disease is represented and articulated in the digital sphere. Expanding on Chavez’s concept of ‘disease-scapes,’ which indicates the build up of signs and symbols that socially construct the conceptualization of various diseases, this study particularly focuses on the establishment of disease-scape on the Zika virus during Rio Olympics. The study observes the Facebook pages of major news media (The New York Times, Wall Street Journal, CNN) and the public discourse happening on this space, which is manifested through the user comments. Examining the constitutive work of multiple texts on Facebook-sphere, the study argues that the visual and discursive images on the Zika outbreak re-appropriated the conventional metaphors on infectious disease by giving them new meanings. While previous literatures on disease discourse detected metaphors that frame immigrants as disease weakening and killing the body of the nation, the new metaphors that compared mosquitoes to immigrants were articulated in the form of satire and parody, in the means to ridicule the political discourse at the time of 2016 presidential election. The paper claims that the commentators are conducting oppositional reading of the previous metaphors, by pointing out the impossibility of containment strategies on global contagions in our contemporary world – while containment and securitization emphasized the imagined boundaries between nation-states and heightened the sense of national identity, the case of Zika virus during the Olympics shows in which such reterritorialization of an infectious disease has failed.